Awareness and Acceptance of PPIUCD among Pregnant Females Attending Tertiary Care Hospital in Pakistan - Amna Javed, Sumera Anjum, Sumaira Fatima Sabir, Fakhrunisa, Saadia Khanam, Zubda Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The postpartum intrauterine contraceptive devices (PPIUCD) is the only family planning strategy for couples asking highly viable, reliable, reasonable, non-hormonal, instantly reversible, and long-acting contraceptive that can be started during the immediate postpartum period and it has no a negative impact on lactation. In spite of this advantage, the acknowledgment and utilization of prompt PPIUCD were exceptionally low and the reasons for dismissing quick PPIUCD utilization have not been characterized in Pakistan. Subsequently, this study determined the level of adequacy and factors related with quick PPIUCD utilize among ladies who gave birth. Methods: A cross-sectional study was conducted from July 2020 to June 2021 at Lahore General Hospital, Lahore. Two hundred females patients were effectively met utilizing structured and pre-tested survey. Health facilities were chosen. Study participants were chosen systematically. Information entered and data was analyzed using SPSS version 23. Calculated relapse examinations were done. A significant association was pronounced at a p-value less than 0.05. Results: Out of these 200 females, 80 females patients (40%) had information of PPIUCD, as it were 30 % of ladies had past information almost PPIUCD however only 8 % of ladies practiced it within the past. After counseling 22% of ladies concurred for addition of PPIUCD after this delivery. Conclusion: The study concludes that the antenatal ladies had poor information with respect to PPIUCD. Practices were indeed more awful. This might be credited to low education, refusal by family particularly male partner, and religious convictions. But once suitable information and data is given, state of mind gradually changes.